A case of spondylodiscitis by Ureaplasma urealyticum in an immunocompetent adult with spine stabilization - Daniele Piccinini; Enos Bernasconi; Gladys Martinetti Lucchini; Caroline Di Benedetto; GianMarco Colombo; Marco Bongiovanni (International Journal of Infectious Diseases, 2023)
ABSTRACT: Ureaplasma urealyticum is part of the normal genital flora of many sexually experienced people, thereby it is mostly associated with genitourinary tract infections. Here, we present the first case reported in the literature of spondylodiscitis caused by U. urealyticum in a 62-year-old immunocompetent subject. U. urealyticum was detected through broad-range bacterial polymerase chain reaction in all samples obtained by T11 bone biopsy, while cultures were all negative. Due to the technical difficulties in removing the spinal osteosynthesis devices, no neurosurgical intervention was planned, therefore a suppressive therapy with moxifloxacin was administered. After 7 months, the patient underwent T10-11 partial vertebrectomy, insertion of an expandable cage at that level, the substitution of T11 screws, and prolongation of stabilization from T6 to ilium due to a fracture of T11 and T12; the remaining spinal osteosynthesis material was not removed. A computed tomography scan of the spine did not show features compatible with spondylodiscitis. Moxifloxacin was stopped after 15 months without any recurrence of U. urealyticum infection. Our case highlights the importance of considering U. urealyticum as a potential etiological germ in culture-negative spondylodiscitis.